Digital Diorama system for museum exhibition - Hayashi, O; Kasada, K; Narumi, T; Tanikawa, T; Hirose, M (2010 9th IEEE International Symposium on Mixed and Augmented Reality, 2010)
In this paper, we proposed the Digital Diorama system to convey background information vividly. The system superimposes computer generated diorama scene reconstructed from related image/video materials on real exhibits. In order to switch and superimpose real exhibits and past photos seamlessly, we implement a matching system for estimating the camera position where photos are taken. By applying this subsystem to 26 past photos about the steam locomotive exhibit, we succeeded in estimating their camera position. Thus, we implement and install a prototype system at estimated position to superimposing virtual scene and real exhibit in the Railway Museum.